Dirty Work
XI, 274 p.
Keywords: This book explores understandings and experiences of 'dirty work' – tasks or occupations that are seen as disgusting and degrading. It complicates the 'clean/dirty' divide in the context of organizations and work and illustrates some of the complex ways in which dirty work identities are managed.